WO3-decorated ZnO nanostructures for light-activated applications. Issue 9 (12th February 2018) - Gasparotto, Alberto; Carraro, Giorgio; Maccato, Chiara; Sada, Cinzia; Balbuena, José; Cruz-Yusta, Manuel; Sánchez, Luis; Vodišek, Nives; Lavrencic Štangar, Urška; Barreca, Davide
Abstract : Calyx-like ZnO nanostructures decorated by WO3 nanoparticles are investigated for NO X degradation and self-cleaning end-uses. Abstract : In the present work, a two-step vapor-phase route was implemented for the tailored design of ZnO–WO3 nanoheterostructures supported on fluorine-doped tin oxide (FTO) substrates. Under optimized conditions, the sequential use of chemical vapor deposition (CVD) and radio frequency (RF)-sputtering for the deposition of zinc and tungsten oxides respectively, resulted in the growth of calyx-like ZnO nanostructures uniformly decorated by a conformal dispersion of low-sized WO3 nanoparticles. The target materials were characterized by means of a multi-technique approach, with particular regard to their structural, compositional, morphological and optical properties. Finally, their photocatalytic performances were preliminarily tested in the abatement of NO X gases (NO and NO2 ). Due to the unique porous morphology of the ZnO nanodeposit and the high density of ZnO–WO3 heterojunctions, WO3 -decorated ZnO revealed appealing De-NO X characteristics in terms of both degradation efficiency and selectivity. Such features, along with the photoinduced superhydrophilicity and self-cleaning properties of the present nanomaterials, candidate them as promising functional platforms for applications in smart windows and building materials for environmental remediation.